Wet‐Spinning and Carbonization of Lignin‐Polyvinyl Alcohol Precursor Fibers. (18th September 2019) - Föllmer, Marie; Jestin, Simon; Neri, Wilfrid; Vo, Van Son; Derré, Alain; Mercader, Célia; Poulin, Philippe
Abstract: Lignin is a promising bio‐based precursor for sustainable carbon fibers. Limiting factors for their development include the brittleness of lignin and the lack of large‐scale production routes. Here, a simple and economic wet‐spinning method, suitable for the fabrication of fibers based on softwood Kraft lignin (KL) and polyvinyl alcohol (PVA), is proposed. These two polymers reveal a partial miscibility in solution, and form metastable dispersions in solid state. KL‐PVA fibers are prepared at a weight ratio of 70:30 and are carbonized without thermo‐stabilization. A tailor‐made temperature program leads to a decreased microporosity on the fiber surfaces. The obtained carbon structures at 1000 °C are found to be poorly ordered, leading to only intermediate mechanical and electrical properties. However, graphitic domains appear at temperatures above 1500 °C and indicate a high potential for the system. Abstract : A simple and economic method is proposed to make biosourced precursor systems for low cost carbon fibers. The method consists in mixing lignin and polyvinyl‐alcohol in solution, and to wet‐spin the solutions. The precursor fibers are carbonized at high temperature, without thermo‐stabilization, to minimize the processing cost. Graphitic domains appear at temperatures above 1500 °C and indicate the high potential of the system.